The impact of socioeconomic characteristics and land use patterns on household vehicle ownership and energy consumption in an urban area with insufficient public transport service – A case study of Metro Manila - Rith, Monorom (Animo Repository, 2019)
Understanding the impact of household characteristics and land use attributes on household vehicle ownership and usage decision is an efficient way of crafting strategic approaches having negative impacts on private vehicle dependency toward a sustainable urban transportation system. This empirical study applied the Gaussian copula-based discrete-continuous choice model to develop an integrated household vehicle ownership and energy consumption model using the unique data sample of 1795 households gathered in 2017 through various areas in Metro Manila, Philippines. The findings necessarily reported that household income is the main factor of household vehicle ownership and energy consumption decision. Households with the presence of older and well-educated household heads are found to be willing to acquire more vehicles. Encouraging urban densification, improvement of road public transport line density, reduction of distance from a residential area to the shortest railway station, and increasing mixture of integral facilities in neighborhoods (i.e., hospitals, markets, schools, and recreation centers) have considerable contributions to build a metropolis with less private vehicle dependency. The developed model was then applied to simulate percentage changes of the vehicle fleet and energy consumption based on various scenarios, and the policy implications based on the empirical findings were also discussed to help policymakers. © 2019 Elsevier Ltd